Analysis of perinatal mortality in Northern Lima: Using the BABIES method - Chan, Luz E. (2019)
Objective: To identify the "opportunity gap" with the BABIES method using perinatal mortality rates. Materials and methods: A descriptive cross-sectional study was performed with the Perinatal and Neonatal Epidemiological Surveillance Database. Perinatal mortality rates by districts and by areas of possible intervention were determined according to the BABIES method. Results: The district of Independencia had the lowest mortality rate, with 6.1 and 5.9 per 100 live births in the years 2014 and 2015, respectively. The priority area of intervention in the district of Comas was "maternal health" and in Carabayllo, "care during pregnancy". Conclusions: The BABIES method allows us to identify the "opportunity gap" which can guide us to perform interventions at the local level.